Показники та критерії в системі вартісно-орієнтованої концепції менеджменту - Яремко, І. Й. (Видавництво Львівської політехніки, 2015)
Розглянуто зміст вартісних критеріїв в оцінюванні ефективності функціонування підприємства та їх використання у вартісно-орієнтованій концепції менеджменту. Проаналізовано контекст компарабельності і якісної характеристики показників та індикаторів у системах і моделях створеної вартості підприємством. Окреслено можливості інтеграції інструментарію вимірювання вартісних параметрів і традиційних фінансових показників. The content value criteria in evaluating the efficiency of companies and their use in valueoriented management concept. Komparabelnosti context analysis and qualitative characteristics and performance indicators in systems and models created value now. The possibilities of integration tools for measuring cost parameters and traditional financial indicators. It is proved that in today's economy expressive tendencies evaluating the effectiveness of the company is profitable transition from the concept of measurement of accomplished effective paradigms to estimates by cost criteria, and taking into account the future (anticipated) market position of the company. Ensuring the growth of value in terms of the global capital market is seen through maximizing the market value of its equity and recognized priority financial management company. Argued that enterprises of the national economy one of the reasons that hinder the formation of a system of evaluation indicators, considered the lack of substantial research and development in coordination with methodological support and parameter validity key value drivers and their criterion values. The basic principles of the software and its components should take into account the indicative characteristics and trends of internal and external environment of domestic enterprises. Adaptation of the proposed models to real conditions of practice enterprise, ie identifying key growth factors value (market) equity based industry characteristics and general economic environment in which the company operates, the transnational nature of the market segment, and further major unsolved problem is the value paradigm. Based on the study concluded that the theory of finance and financial management obviously put forward a rational criterion value (market capitalization growth or the market value of equity) now measure its efficiency in the current economic environment. However, in spite of sufficient detelnu dokdadno contained and logical-wide basis and methodological basis, output specification theoretical foundations and empirical evaluation of existing models and systems management cost criteria need significant improvements. Therefore, there are considerable reservations theoretical and methodological plan and sufficient empirical data on the probability of the presently known systems and models for measuring the cost parameters of the company. Due to the fact that each of the considered parameters has its limitations and shortcomings, and that the scope of cost indicators is a relatively new branch of knowledge, many economists (theoreticians and practitioners) offer their own versions of the combined use of several indicators of the evaluation process of value creation. It is proved that the selection process of cost factors and performance indicators for the formation of the national system for evaluating the effectiveness of cost criteria should form based on scientific calculations, taking into account the specific features of the enterprise sector and some specific conditions in the economy. The following content characteristics cost indicators and indicators can be taken into account in the future implementation of the fundamental themes of national development of cost evaluation system.
Criteria and indicators in value -oriented concepts management
Keywords: показники; індикатори; критерії; фактори вартості; системи і моделі виміру вартісних параметрів підприємства; показники прибутковості; performance indicators; criteria and cost factors; systems and models measuring cost parameters enterprise profitability